Pengaruh Kemampuan Kerja dan Tunjangan Kesejahteraan Terhadap Kinerja Pegawai Pada PT. PLN (Persero) Rayon Medan Johor - Eva Ramayani; Wan Suryani; Dahrul Siregar (Universitas Medan Area, 2020)
The purpose of this study was to determine the Effect of Work Ability and Welfare Benefits on Employee Performance at PT. PLN (Persero) Rayon Medan Johor. This type of research is associative research that connects two or more variables. The population used in this study was 58 people. The results showed that partially the coefficient regression variable Working Ability tcount t table (5.907 2.004), and the significance value was smaller than the probability value (0.000 0.05). This means that the variable work ability has a significant effect on employee performance. Partially Welfare Benefits t on the table value (10,685 2,004), and the significance value is smaller than the probability value (0,000 0.05) means that the Welfare Benefit variable has a partial effect on Employee Performance. Simultaneously shows that the variable work ability and welfare benefits significantly influence employee performance because the value of Fcount = 89.725, while Ftable is 3.16, thus Fcount (89.725) Ftable (3.16) with a Sig. F is 0,000. The coefficient of determination is 0.765, this shows that the variable ability of Work Ability and Welfare Benefits is able to explain that Employee Performance is 76.5% and the remaining 23.5% is influenced by other variables outside this study.